A new species and notes on Perlidae (Plecoptera) from Paraná and Santa Catarina States, southern Brazil - Novaes, Marcos Carneiro; Bispo, Pitágoras Da Conceição (Zootaxa, 2014)
Specimens of Perlidae (Plecoptera) deposited in the Entomological Collection "Padre Jesus S. Moure" of the Universidade Federal do Paraná and additional material recently collected in Paraná and Santa Catarina states, Brazil were studied. Six previously described species were identified, Anacroneuria debilis (Pictet, 1841), A. cathia Froehlich, 2002, A. polita (Burmeister, 1839), A. trimacula Jewett, 1959, Kempnyia neotropica (Jacoson and Bianchi, 1905) and K. colossica (Navás, 1934). Additionally, a new species, Anacroneuria iguazu n. sp is described.